GG HPS-2: A high yielding and large seeded Virginia bunch groundnut (Arachis hypogaea L.) variety for Gujarat state: GG HPS-2: A high yielding and large seeded Virginia bunch groundnut (Arachis hypogaea L.) variety for Gujarat state - G K SAPARA,; V H KACHHDIYA,; C J RAJANI,; K L DOBARIYA, (Journal of Oilseeds Research, 2023)
A Virginia bunch large seeded groundnut variety GG HPS 2 was developed from the cross JVB HPS 2 and GG 20. It recorded a higher mean pod yield (2835 kg/ha) and kernel yield (1945 kg/ha) as compared to the checks. GG HPS 2 recorded an average 100 kernel weight of 66.71 g, shelling out-turn of 68.61% and oil content of 48.82%. GG HPS 2 showed restistance reaction to tikka (leaf spot) and rust reaction, whereas it showed comparable resistance to stem rot, collar rot, damages due to leaf defoliators and thrips under field conditions with check varieties. Based on the superior performance, it has been released for kharif groundnut growing areas of the Gujarat State.